2021
DOI: 10.1016/j.isci.2020.101900
|View full text |Cite
|
Sign up to set email alerts
|

NLRC5 promotes transcription of BTN3A1-3 genes and Vγ9Vδ2 T cell-mediated killing

Abstract: Summary BTN3A molecules—BTN3A1 in particular—emerged as important mediators of Vγ9Vδ2 T cell activation by phosphoantigens. These metabolites can originate from infections, e.g. with Mycobacterium tuberculosis, or by alterations in cellular metabolism. Despite the growing interest in the BTN3A genes and their high expression in immune cells and various cancers, little is known about their transcriptional regulation. Here we show that these genes are indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 65 publications
4
14
0
Order By: Relevance
“…In contrast, CRISPR/Cas9-mediated knockout of BTN3A molecules almost eliminated the enhanced lethality induced by NLRC5 overexpressing cells. This new discovery about the relationship between BTN3A family and NLRC5 further discusses the mechanism of BTN3A family in the activation of Vγ9Vδ2 T cells, and brings more implications for the study of immunotherapy 69 .…”
Section: Conclusion and Prospectmentioning
confidence: 84%
“…In contrast, CRISPR/Cas9-mediated knockout of BTN3A molecules almost eliminated the enhanced lethality induced by NLRC5 overexpressing cells. This new discovery about the relationship between BTN3A family and NLRC5 further discusses the mechanism of BTN3A family in the activation of Vγ9Vδ2 T cells, and brings more implications for the study of immunotherapy 69 .…”
Section: Conclusion and Prospectmentioning
confidence: 84%
“…A recent report from the Guarda laboratory has implicated NLRC5 in activating γδ T cells via inducing the expression of butyrophilin (BTN) family proteins BTN3A1-3 [ 175 ]. γδ T cells express TCR with limited diversity that recognize self-MHC proteins in an innate-like fashion independently of their peptide cargo.…”
Section: Induction Of Butyrophilins By Nlrc5 and γδ T Cell Activatmentioning
confidence: 99%
“…The human BTN family genes reside within the MHC locus on chromosome 6 and Btn2a2 is regulated by CIITA via the SXY module [ 179 ]. Guarda and colleagues showed that human BTN3A genes ( BTN3A1 , BTN3A2 , BTN3A3 ) also harbor the SXY module, and their expression positively correlates with NLRC5 [ 175 ]. NLRC5 was shown to bind the promoter region of BTN3A and induce its expression, suggesting a potential role for NLRC5 in immune homeostasis.…”
Section: Induction Of Butyrophilins By Nlrc5 and γδ T Cell Activatmentioning
confidence: 99%
See 1 more Smart Citation
“…For the molecular cloning of the pHRSIN-CS-Luc-IRES-mTagBFP2 vector, the previously described pHRSIN-CS-Luc-IRES-emGFP vector (a kind gift from A. Rodriguez, Universidad Autonoma Madrid, Spain) was digested with BstX1 and Not1 restriction enzymes to remove the emGFP. mTagBFP2 was amplified from the previously described pHRSIN-CS-IRES-mTagBFP2 plasmid (Dang et al, 2020) and BstX1-and Not1-specific overhangs were added using PCR. The final expression vector was generated by Gibson assembly using the pHRSIN-CS-Luc-IRES as recipient vector and the amplified mTagBFP2 as insert.…”
Section: Molecular Cloning Of the Luciferase-bfp And S Protein-mscarlet Vectorsmentioning
confidence: 99%